Intrinsic capacity and its change predict cardiovascular disease risk in early cardiovascular-kidney-metabolic syndrome: a nationwide cohort study - Fei Song; Meng-Jin Hu; Jinggang Xia; Chunlin Yin (Open Heart)
Background Cardiovascular-kidney-metabolic (CKM) syndrome plays a critical role in the pathogenesis of cardiovascular diseases (CVD). Growing evidence has established that impaired intrinsic capacity (IC) served as a robust predictor of adverse health outcomes. However, its specific association with incident CVD in CKM syndrome populations has not been established.Methods The China Health and Retirement Longitudinal Study is a nationally representative cohort study in China. First, the relationship between baseline IC and the incidence of CVD was analysed using Cox regression models. Subsequently, subgroup and interaction analyses were conducted among different groups. To investigate the potential non-linear relationship between baseline IC and CVD risk, restricted cubic spline (RCS) regression of HR was employed. Furthermore, IC trajectories over time were analysed using group-based trajectory modelling. The associations of the trajectory memberships with CVD risk were analysed using logistic regression models.Results Among 5346 participants included, of whom 2712 (50.7%) were men and 2634 (49.3%) were women, with a mean age of 57.3 (9.02) years. The results of the fully adjusted Cox regression analyses indicated that there was an 8% decrease in risk for every 1-score rise in IC (HR=0.92, 95% CI: 0.87 to 0.98). The RCS regression analyses demonstrated a linear association between baseline IC and CVD risk in the CKM syndrome population. Subgroup and interaction analyses showed no interactions observed in any subgroups. Trajectory analysis identified three longitudinal patterns of IC with age: class 1, ‘low level’ (12%); class 2, ‘medium level’ (25%); class 3, ‘high level’ (63%). Logistic regression models indicated that both ‘low level’ and ‘medium level’ IC trajectories were independently associated with significantly higher CVD risk compared with the ‘high level’ reference group.Conclusions This prospective cohort study demonstrated significant associations between both baseline IC and its longitudinal changes with incident CVD risk among individuals with CKM syndrome stages 0–3.